THE EFFECT OF COMPETENCE AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH WORK SPIRIT AS AN I NTERVENING VARIABLE (Case Study of PT Moeis Perkebunan Sipare Pare) - Novitasari, Ela; Nurpadilla, Nurpadilla; Siahaan, Rumiris; Khairunnizar, M. Alang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to The Influence of Competence and Motivation on Employee Performance with Work Spirit as an Intervening Variable Pabatu Case Study at PT Moeis Kebun Sipare-pare. The research method used is a quantitative method using the help of SPSS version 25.00. which was collected from the results of distributing questionnaires to PT Moeis Kebun Sipare-pare Plantation Employees as many as 50 respondents. The analysis method used in this study is to use an instrument test, namely validity and reliability tests. Classical assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis tests, namely the T test and path analysis. The results of SPSS in this study are that work experience variables affect work motivation, competence affects work spirit, motivation affects work spirit, competence affects performance, motivation does not affect performance, work spirit affects employee performance, competence affects employee performance with work spirit as an intervening variable motivation affects employee performance with work spirit as an intervening variable. Keywords: Competence, Motivation, Work Spirit, Employee Performance